The use and associated constraints of urban greenery from socioelogical perspective: a systematic review - Paneerchelvam, Patheeba; Maruthaveeran, Sreetheran; Maulan, Suhardi; Abd. Shukor, Shureen Faris (Elsevier, 2020)
There are studies claiming that the use of greenways is highly influenced by personal, social, and physical attributes. Nonetheless, there is a lack of systemic reviews that have synthesized the evidence. This study systematically reviews the literature to gather evidence related to the types of attributes and constraints affecting the use of urban greenways. The literature reviewed was published between 2000 and 2018. The findings from the review could be assimilated into some recommendations for future researchers. The review adapted the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement guidelines in reporting systematic reviews and meta-analysis.Keywords linked to greenways and their constraints were researched by two independent reviewers. A total of 45 publications were published between 2000 and 2018 (N = 45) that met all the selection criteria for the systemic review. The studies were carried out in America, the United Kingdom, Australia, Germany, Turkey, Japan, and China, with respondents ranging from 21 to 17,338. These studies were heterogeneous in their design, population, urban greenway assessment, and data. From the review, it was found that most studies concluded that the use of greenways was highly influenced by personal, social, and physical attributes. Weather and time of day also influenced users’ decision to use the urban greenways. Nevertheless, the factor of time was not highlighted in most of the studies. Following this, more studies are needed on the role of time of day (day or night). This review agrees that users’ decisions to use greenways are influenced by physical, social and personal attributes. More studies focusing on users’ choices and decisions to use greenways are necessary to provide sensible and practical ways of improving urban greenways based on the population’s preferences. Apart from that, more researches on the factor of time would be beneficial.